THE MAKING OF SMART PENCIL CASE TO LEARN ENGLISH VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - -, nur'afni; Saputra, Boni (Politeknik Negeri Bengkalis, 2023)
Abstact : The idea of this project came up when in the real concept; the students actually still face difficulties and lack interest in mastering English, including memorizing English vocabulary. there are many same words but different pronounce This condition students create uncomfortable the use of learning media in learning will surely help these learners understand the lesson well and give back their interest . The main purpose of this final project is to make Smart Pencil case which can be used as an alternative self-learning medium in learning vocabulary. The Method was using in this final project is classified to descriptive which was animal to describe of creating of creating a smart pencil case as a learning media the resulted of this final project a four of Smart pencil case consists of different themes. This media can be used in and out classes during learning-teaching process or spare time. By using this media, the students can learn and increase their interest in learning English vocabulary with more interesting and effective way. Keywords: Smart pencil case, vocabulary, elementary school students